Adsorption and diffusion behavior of two-component gases in coal particles at different temperatures. (1st May 2023) - Liu, Wei; Chu, Xiangyu; Qi, Minghui; Han, Dongyang; Zhang, Shixian; Qin, Yueping
Highlights: Temperature has a strong influence on the adsorption of two-component gas mixtures and their cumulative adsorption satisfies our proposed empirical equation; The FDGD model is applicable to express the diffusion behavior of strongly adsorbed single-component gas in two-component mixtures under different temperatures; The microchannel diffusion coefficients ( Fm ) of the single component gas increases with increasing temperature. Abstract: Oxygen (O2 ) plays a crucial role in the occurrence and progression of coal spontaneous combustion (CSC), but the diffusion behaviors of O2 and oxygen-containing gas mixtures (e.g., CO2 -O2 ) in the microchannels of coal under different temperatures have involved little investigation. In this work, isothermal adsorption experiments of two-component gas mixtures at different temperatures (293 K-333 K) were first carried out. A two-component gas mixture adsorption model for coal particles based on the free gas density gradient (FGDG) diffusion was then developed. The cumulative gas adsorption was obtained by numerical solution and the microchannel diffusion coefficients ( Fm ) of single-component gases in gas mixtures were obtained by comparing the simulation results with the experimental data. The results show that: (i) the equilibrium cumulative adsorption of three types of gas mixtures decreases with the increase of temperature, and their cumulative adsorption satisfies our proposed empirical equation; (ii) the simulation results of strongly adsorbed single-component gases are in high agreement with the experimental data throughout the adsorption period, and the developed model is verified. It also indicates that the model can characterize the migration behavior of single-component gas in coal particles under different temperature conditions; (iii) the Fm of a single-component gas will gradually increase as the temperature increases, leading to further enhancement of diffusion behavior of the gas. This research is expected to provide some theoretical foundations for understanding the mechanisms of gas mixtures flowing in coal matrices under different temperature environments.